(untitled) (The International Journal for Scientific Research, 2025)
This study tried to identify the attitudes of Sultan Moulay Slimane students in Béni Mellal towards international migration. To achieve the research objectives, a scale of attitudes was built according to the Likert scale and the use of SPSS for statistical analysis to ensure the validity and reliability of the study tool and to detect the differences for a sample of 150 students using the questionnaire and the descriptive approach. This research relied on the IMRAD methodology, which is characterized by the clarity of its stages to reach the research objectives with correct, logical and sequential steps. - The most important results of the study were as follows: - There are statistically significant differences at the level of α ≤ 0.05 in the attitudes of Béni Mellal students towards emigration due to the variables of age, marital status, education level, and professional status; - There are statistically significant differences attributed to the gender and college variables; - The most preferred destination is the USA (26%), followed by France (23.3%); - Unwillingness to emigrate is due to lack of means (44%), not leaving one’s family (34%), and lack of opportunity for legal emigration (31%).